Прикладна лінгвотермінографія в типологічному аспекті - Казимирова, І.А. (Мовознавство, 2017)
У статті проаналізовано здобутки прикладної лінгвотермінографії — мовознавчої дисципліни, орієнтованої на укладання словників лінгвістичних термінів. Схарактеризовано базові поняття, за якими здійснюють розподіл лексикографічних творів; показано особливий статус термінологічних словників, який полягає в поєднанні ознак філологічних і енциклопедичних словників. Подано аналіз словників лінгвістичних термінів з огляду на їхнє місце в класифікації праць цього жанру. The achievements of applied lingvoterminography is analized in the article. It is a linguistic discipline which deals with composing dictionaries of linguistic terms. Some scientific works on the problems of vocabulary typology and its classification in general are reviewed. Author determined basic concepts, which carry out the distribution of lexicographical works. The special status of terminological dictionaries is shown, which is a combination of signs philological and encyclopedic dictionaries.
This article contains information about the genre origin of the linguistic dictionaries. The first such dictionary in Ukraine is «Historical Dictionary of Ukrainian Grammar Terminology» by 1.1. Ogiyenko. Author describes some modem views on classification of terminological dictionaries of linguistic terms. According to the type register allocated dictionaries of extensive type with the complete list of linguistic terms; dictionaries of intensive type; foreign-native-foreign language dictionaries. According to the vocabulary material - lexicons and thesauri; according to the degree of dictionary entry descriptiveness - explanatory and nomenclature (indexes, term lists) dictionaries and glossaries; explanatory dictionaries can be encyclopedic and explanatory dictionaries. The perspective directions of lexicography in linguistics are shown. The analysis of linguistic dictionaries are given according to their place in the classification of the works of this genre.